2009
DOI: 10.1089/gtmb.2008.0045
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Methylation in the Promoter of APC and MGMT and the Prognosis of Taiwanese CRC Patients

Abstract: Methylation in the APC promoter may serve as a predictor for the prognosis of Taiwanese CRC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 15 publications
2
24
2
Order By: Relevance
“…16 APC hypermethylation is also frequent in sporadic CRC and may cause transcriptional silencing occurring early during colon neoplasia progression, but the reported methylation status of the APC promoter varies greatly among studies performed in different populations. [16][17][18][19] Moreover, hypermethylation of the APC promoter has been shown to be relatively common in the normal colonic mucosa. 19 Present results are in agreement with recent reports in Swedish and Vietnamese CRC patients, where methylation of the APC gene was detected with similar frequencies between the cancerous and normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…16 APC hypermethylation is also frequent in sporadic CRC and may cause transcriptional silencing occurring early during colon neoplasia progression, but the reported methylation status of the APC promoter varies greatly among studies performed in different populations. [16][17][18][19] Moreover, hypermethylation of the APC promoter has been shown to be relatively common in the normal colonic mucosa. 19 Present results are in agreement with recent reports in Swedish and Vietnamese CRC patients, where methylation of the APC gene was detected with similar frequencies between the cancerous and normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The reported methylation status of the promoter of APC varies greatly among studies of CRC in different populations (16)(17)(18)(19)(20). Moreover, hypermethylation of the APC promoter has been shown to be relatively common in other gastrointestinal neoplasms, including those of the stomach, liver, pancreas and oesophagus (17,29).…”
Section: Discussionmentioning
confidence: 99%
“…The APC promoter methylation rate has been detected in CRC and normal colorectal mucosa at a range of 11 to 62% in different populations, and has been suggested to moderate the Wnt signalling pathway (16)(17)(18)(19)(20). Studies have indicated that IGFBP7 is inactivated by DNA methylation in human colon, lung and breast cancer (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Loss of APC function results in nuclear accumulation of β-catenin, which leads to the transcriptional activation (via the β-catenin/T-cell factor complex) of target genes that may contribute to colorectal tumorigenesis (23,24). The rate of APC promoter methylation in CRC and normal colorectal mucosa has been reported to range from 11 to 62% in different populations, and has been suggested to moderate the Wnt signaling pathway (25)(26)(27)(28)(29). Furthermore, hypermethylation of the APC promoter has been demonstrated to be relatively common in other gastrointestinal neoplasms, including those of the stomach, liver, pancreas and oesophagus (30).…”
Section: Introductionmentioning
confidence: 99%